Enhanced control to mitigate “faults” of mems vibratory gyroscopes in aircraft autopilot systems - Akorli, David (University of Mines and Technology, 2020)
Aircraft autopilots are automatic flight control and stabilisation systems. A segment of the autopilot is the pitch control system that is responsible for up or down movement of the aircraft about its lateral axis. One militating factor of hitherto existing pitch control systems is the faults of relatively large sized mechanical or other deployed gyroscopes that are capable of malfunctioning the aircraft autopilot system. In this research, the small sized and cheaper MEMS vibratory gyroscope has been investigated by modelling and simulation for temperature and noise effects and deployed as an angular rate sensor in the pitch control system. MEMS vibratory gyroscope output signal response stood at  5% at 12.5 dps and 33 dps instead of the accepted standard value of  2% . The temperature and noise effects as “faults” affected the performance of the MEMS vibratory gyroscope. PI, PID. Fuzzy-PI, fuzzy-PID and ANFIS controllers were then used to mitigate the effect of the oscillations at the output of the MEMS vibratory gyroscope on the pitch control system. The ANFIS and the two fuzzy controllers did well but settled with remnant oscillations. Particle swarm optimisation and flower pollination algorithms were deployed to optimise the three controllers. The particle swarm optimisation combined with ANFIS controller successfully eradicated the temperature and noise effects on the pitch control system. Additionally, it performed better than the other options in terms of overshoot and settling time. Subject to further research, MEMS vibratory gyroscopes stand to be deployed effectively in aircraft autopilot systems to contribute to global safety in the aviation industry.
xviii; 133p
Keywords: Aviation industry; Piloting systems; Aeronautical engineering; Avionics